Diretrizes MobiDeaf: uma abordagem para desenvolvimento de aplicações de redes sociais em dispositivos móveis para os surdos - Schefer, Ricardo Pezzotti (Universidade Federal de São Carlos, 2016)
The easy access to mobile and social networking is changing the way people communicate; however, the deaf person is segregated in some of these media. Although there are many designers working with some recommendations, these are still too general and do not satisfy the complete interaction of the deaf in these environments. In this scenario, the deaf audience is not considered in the creation of these applications either because the developers do not know or because they cannot find direct and accurate information about the needs of this group. Supported by literature and experiments, this paper proposes guidelines for developing applications for social networks on mobile devices specifically focused on the deaf audience. Through action research approach (AR), at first we tried to know the difficulties of the public from the perspectives of interaction with mobile devices applied to social networks, specifically Facebook. This first AR cycle was carried out through tests with users for Communicability Evaluation Method (CEM). Afterwards, one participatory design session (DP) was performed, in which the prototypes produced by the users were analyzed and classified by the Model 3C vision. Based on guidelines and the results of experiments, the MobiDeaf was created with eight guidelines. Mobideaf was evaluated by comparison with the WCAG 2.0 recommendations in two types of tests: (i) with designers who produced prototypes, which were analyzed, inspected and reproduced in a test application, and; (ii) with deaf people who experimented the test application. This project contributes in bringing a set of guidelines that help both the designer and the target audience. Also describes CEM tests and a DP session. Presents a mapping of the features worked by the deaf based on Facebook social network, in the Model 3C. Shows in detail the creation and evaluation of guidelines that can be used to enable better interaction of the deaf with society in general through social networking on mobiles.
MobiDeaf Guidelines: an approach to developing social networking applications in mobile devices for the deaf
Keywords: Redes sociais; Social networks; Surdos; Deaf; Interface de programas aplicativos (Software); Application program interfaces (Computer software); Aplicativos móveis; Mobile apps; Design participativo; Participatory design; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO